Implementation Of Handling Imported Goods Activities In The Bonded Warehouse Of PT. Sunjaya Mentari Abadi Semarang - Noni Fitri Febriana; Pambudi, M Aji Luhur; Ali Khamdilah (Nama Jurnal Akmi, 2024)
This research aims to optimize the handling of imported goods and the management of fabric documents to improve the quality of bonded warehouse services at PT Sunjaya Mentari Abadi Semarang. The method used in this study is a qualitative approach with descriptive analysis, which involves direct observation, interviews, and documentation studies. This study identifies inefficiencies in handling goods and document management and their impact on service time and customer satisfaction.  The results show that implementing optimization strategies, including increased coordination between departments and using more efficient information systems, can significantly improve the quality of bonded warehouse services. The study recommends system improvements that reduce wait times, improve document accuracy, and improve customer satisfaction. These findings are expected to be the basis for companies to formulate better policies in managing imported goods and documents